Consequences of Thumb Sucking Habit among School Going Children: A Cross Sectional Study - Huda Mannan; Anam Ahmed; Khandakar Nuruzzaman; Suman Hossain; Nusrat Tamij (Update Dental College, 2023)
Background: Thumb-sucking, a non-nutritive sucking behavior, is a natural reflex seen in infants but can persist into childhood if not addressed leading to various dental and orofacial issues, including malocclusion, dental arch deformities, speech difficulties, and facial asymmetry. The aim of the study was to explore the consequences of thumb-sucking habits among the school going children. Methods: This cross-sectional study involved among purposively selected 124 school going children, aged between 5-8 years with their parents attended in the outpatient department of University Dental College at Moghbazar, Dhaka, Bangladesh. The data were obtained through a pretested structured questionnaire and checklist through face-to-face interview from parents regarding background characteristics, consequences of thumbs sucking and oral examination of children respectively.  Then, data were analyzed using statistical package for social sciences (SPSS) software version 27 for descriptive analysis (frequency, percentage) and inferential statistics (chi-square test or fisher's exact test)  at 5% level of significance (P<0.05).  Results: The study revealed that 77.4% of children aged 5-6 years and about 41.9% of parents reported that their child had thumb sucking habit. The thumb sucking habit was found to be statistically significant with start of age thumb sucking( p= <0.001), duration of thumb sucking ( p= <0.001), pronunciation of word clearly( p= <0.001), proclination of maxillary anterior teeth (P=0.002), asymmetry of face (P=0.002) and seek for dental advice or treatment(p=0.002). Majority of children (21.8%) start thumb sucking at the age 6-7 years. Only 8.1% of the children didn't pronounce words clearly whereas only 5.6%  had proclined maxillary anterior teeth, facial asymmetry and sought dental advice or treatment. Conclusion:  This study found a significant association of thumb-sucking habit among children with notable consequences. It highlights the importance of early intervention and parental education and  awareness regarding this habit's potential consequences on children's oral health and overall development. Update Dent. Coll. j: 2023; 13(2): 19-22